1996
DOI: 10.1111/j.1349-7006.1996.tb03153.x
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and Characterization of Human Gastric Carcinoma Lines with High Metastatic Potential in the Liver: Changes in Integrin Expression Associated with the Ability to Metastasize in the Liver of Nude Mice

Abstract: There is a need to establish animal models which are suitable for investigation of human gastric cancer metastasis to the liver. To this end, a human gastric carcinoma line, AZ521 was injected into the spleens of nude mice. Cells from the few liver metastatic foci of injected AZ521 were expanded in vitro and subsequently injected into the spleens of nude mice. By repeating these procedures three times, we were able to obtain a cell line, designated as AZ‐M3c, with high metastatic potential in nude mice. Liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0

Year Published

1997
1997
2002
2002

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 36 publications
0
39
0
Order By: Relevance
“…Ura et al ( 1996), in contrast to our study, demonstrated that the expression of ICAM-1 was inversely correlated with liver metastasis. Yasoshima et al (1996) also showed a reduced expression of ICAM-I and of LFA-1 and increased surface expression of P1 integrins in an experimental animal model of high-metastatic gastric cancer cell line.…”
Section: Discussionmentioning
confidence: 87%
“…Ura et al ( 1996), in contrast to our study, demonstrated that the expression of ICAM-1 was inversely correlated with liver metastasis. Yasoshima et al (1996) also showed a reduced expression of ICAM-I and of LFA-1 and increased surface expression of P1 integrins in an experimental animal model of high-metastatic gastric cancer cell line.…”
Section: Discussionmentioning
confidence: 87%
“…We examined the expression of syntenin mRNA and protein in various gastric cancer cell lines (Figure 1b). Expression of syntenin mRNA and protein was elevated in SNU-5, -216, -620 and -638 cells, which are established from secondary tumor sites and metastatic (Park et al, 1990(Park et al, , 1997, compared with SNU-1, -484 and Az-521 cells, which are from the primary tumor and poorly metastatic (Park et al, 1990(Park et al, , 1997Yasoshima et al, 1996). Also, we analysed the mRNA expression of syntenin in gastric tumor tissues by Northern blot analysis (Figure 1c).…”
Section: Expression Analysis Of Syntenin In Various Human Breast and mentioning
confidence: 99%
“…AZ-H5c is a highly liver metastatic cell line derived from AZ-521, and was previously reported. 9,10) The cell line was maintained in RPMI 1640 medium supplemented with 10% fetal calf serum (FCS) (Sigma, St. Louis, MO), 2 ml L-glutamine, 50 units/ml penicillin and 50 mg/ml streptomycin (Gibco, Grand Island, NY) in a humidified atmosphere of 95% air and 5% CO 2 at 37°C. The cells were passaged and expanded by trypsinization of cell monolayers followed by replating every 4-5 days.…”
Section: Animalsmentioning
confidence: 99%
“…[6][7][8] We also established and reported a highly liver metastatic cell line, AZ-H5c, derived from a human gastric cancer line, AZ-521. 9,10) …”
mentioning
confidence: 99%
See 1 more Smart Citation